Nitrogen, Phosphorus, and Potassium Uptake in Rain-Fed Corn as Affected by NPK Fertilization - Ravinder Singh; Steven Kyle Sawatzky; Matthew Thomas; Samuel Akin; Hailin Zhang; William Raun; Daryl Brian Arnall (Agronomy, 2023)
Effective nutrient management requires understanding nutrient uptake at various growth stages and nutrient removal by the harvested portion. Information on nutrient accumulation was provided by some older literature, and a few researchers have focused on this issue in this modern period with modern hybrids and improved corn cultivation practices. While almost all the studies were conducted in northern states of the US, information for the Southern Great Plains is still limited. To bridge this knowledge gap, a 2-year field study was conducted in a rain-fed corn production system. The study aimed to evaluate the impact of nitrogen (N), phosphorus (P) and potassium (K) fertilization on N, P, and K contents in aboveground plants at different growth stages. Pre-plant application of N (0, 67, 133 kg N ha−1), P (0 and 20 kg ha−1) and K (0 and 60 kg ha−1) fertilizers was done. Results from our study revealed that nutrient uptake values, pattern and dynamics depend on environmental conditions, soil type and management practices. N concentration in plants showed a linear response to N application rate while P and K concentrations were unaffected by NPK fertilization rates. Total N, P and K uptake was primarily driven by N application rate, showing a linear increase with higher N rates. Co-application of P and K with N did not significantly affect nutrient concentration and uptake.